THE INFLUENCE OF GREEN ACCOUNTING IMPLEMENTATION AND ENVIRONMENTAL PERFORMANCE ON FINANCIAL PERFORMANCE - Rahmi, Raisa; Rochayatun, Sulis (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 9 No 1 (2023): The 9th International Conference of Islamic Economics and Business (ICONIES 2023), 2023)
T This research aims to analyze the influence of green accounting and environmental performance on the financial performance of industrial companies in Indonesia. The research population comprises industrial companies listed on the Indonesia Stock Exchange, and a sample of 6 industrial companies is selected from 2020 to 2021. The study employs multiple regression analysis conducted using the SPSS program. Green accounting is evaluated using the dummy method, environmental performance is assessed based on the PROPER evaluation, and Financial performance is assessed through Return on Assets (ROA). The analysis findings suggest that green accounting and environmental performance do not significantly impact financial performance.